Detection of antimicrobial resistance-associated proteins by titanium dioxide-facilitated intact bacteria mass spectrometry. Issue 8 (29th January 2018) - Zhu, Yingdi; Gasilova, Natalia; Jović, Milica; Qiao, Liang; Liu, Baohong; Lovey, Lysiane Tissières; Pick, Horst; Girault, Hubert H.
Abstract : TiO2 -facilitated MALDI–TOF-MS was proposed to improve intact bacteria fingerprinting, allowing rapid and convenient antimicrobial resistance-associated protein detection during bacteria identification. Abstract : Titanium dioxide-modified target plates were developed to enhance intact bacteria analysis by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. The plates were designed to photocatalytically destroy the bacterial envelope structure and improve the ionization efficiency of intracellular components, thereby promoting the measurable mass range and the achievable detection sensitivity. Accordingly, a method for rapid detection of antimicrobial resistance-associated proteins, conferring bacterial resistance against antimicrobial drugs, was established by mass spectrometric fingerprinting of intact bacteria without the need for any sample pre-treatment. With this method, the variations in resistance proteins' expression levels within bacteria were quickly measured from the relative peak intensities. This approach of resistance protein detection directly from intact bacteria by mass spectrometry is useful for fast discrimination of antimicrobial-resistant bacteria from their non-resistant counterparts whilst performing species identification. Also, it could be used as a rapid and convenient way for initial determination of the underlying resistance mechanisms.